ANALISIS KESANTUNAN IKLAN RADIO BERBAHASA JAWA DAN RELEVANSINYA SEBAGAI MATERI AJAR MENDENGARKAN IKLAN KELAS VIII SMP - Nur Huda; Raheni Suhita; Kenfitria Diah Wijayanti (Universitas Sebelas Maret, 2019)
The aimed of this research are (1) To describe politeness in advertisement using Java language; (2) to describe impoliteness in advertisement using Java language and; (3) the relevance of radio advertisement using Java language as teaching material listen advertisement class VIII. Based on the result of thid research can conclude several things: (1) a form of politeness on radio advertising in Javanese form, fulfilling taxt maxim generosity maxim, approbation maxim, modesty maxim, agreement maxim, and simpathy maxim. The use of low Javanese language diversity and proper manners. Use of the word greeting. Use words ‘please’ and ‘thank you’. (2) The form of impoliteness form, breach approbation maxim, agreement maxim, simpathy maxim and taxt maxim. The use of language diversity low Javanese improper. Use of tone not appropriate, selection or improper use of diction. (3) Radio advertisements using Java language is appropriate and relevance to be used as teaching material for competency standards are able to listen and understand spoken discourse in a variety of Java language with basic competence listening advertisement.